A Quantitative Analysis of School-level Factors and Their Impact on the Racial Achievement Gap - (:unkn) unknown (My University, 2016)
Utilizing the National Center for Education Statistics (NCES) Early Childhood Longitudinal Study (ECLS) dataset, I examined the racial composition of schools and classrooms, disciplinary variables, levels of reading and math levels, test scores, and other aspects of schools to analyze effectively the marginal effects of being a black student within schools. Focusing on the dependent variables of test scores, classroom ability level, and suspension rates, I controlled for non-school related factors in order to isolate the impact of school influences on academic achievement, utilizing Hierarchical Linear Models. The results of this study indicate that early school tracking as well as differential disciplinary treatment contribute to the black/white test score gap that has been persistent for decades. This research is important to understand fully the impact of the differential treatment that black students experience within schools. Without research such as this, integration reforms will continue to dismiss key issues within schools that are disproportionately hurting the achievement of black students.
Keywords: Achievement Gap; Black/white Test Score; ECLS; K-8th; School Inequality; Test Score Gap